Experience and Prevalence of Dental Caries in 6 to 12-Year-Old School Children in an Agricultural Community: A Cross-Sectional Study - Juan José Villalobos-Rodelo; Martha Mendoza-Rodríguez; Rosalina Islas-Zarazúa; Sonia Márquez-Rodríguez; Mariana Mora-Acosta; América Patricia Pontigo-Loyola; María de Lourdes Márquez-Corona; Carlo Eduardo Medina-Solís; Gerardo Maupomé (MDPI AG, 2021)
Objective: To describe the experience and prevalence of dental caries in schoolchildren aged 6-12 years belonging to agricultural manual worker households. Material and Methods: A comparative cross-sectional study was conducted in two groups of schoolchildren: One considered "children of agricultural worker migrant parents" (n = 157) and the other "children of agricultural worker non-migrant parents" (n = 164). Epidemiological indices for dental caries were calculated for primary (dmft) and permanent (DMFT) dentitions, and compared in terms of age, sex, and the Simplified Oral Hygiene Index (SOHI). Two binary logistic regression models for caries prevalence in primary and permanent dentitions were generated in Stata. Results: For primary dentition, we observed the following dmft index: Non-migrants = 1.73 ± 2.18 vs. migrants = 1.68 ± 2.14. Additionally, we recorded the following caries prevalence: Non-migrants = 59.1% vs. migrants = 51.3%. For permanent dentition, we observed the following DMFT index: Non-migrants = 0.32 ± 0.81 vs. migrants = 0.29 ± 0.95. Further, we recorded the following caries prevalence: Non-migrants = 17.6% vs. migrants = 12.8%. No differences were observed for either dentition (p > 0.05) in caries indices and their components or in caries prevalence. When both caries indices (dmft and DMFT) were combined, the non-migrant group had a higher level of caries experience than the migrant group (p < 0.05). No relationship (p > 0.05) with migrant status was observed in either multivariate models of caries prevalence. However, age did exhibit an association (p < 0.05) with caries. Only the plaque component of SOHI was associated (p < 0.05) with caries in permanent dentition. Conclusions: Although over half of school children from agricultural manual worker households had caries in either or both dentitions and a considerable proportion were untreated lesions, the prevalence levels were somewhat lower than other reports from Mexico in similar age groups. No statistically significant differences were found in caries experience or prevalence in either dentition between non-migrant and migrant groups.